2018
DOI: 10.26552/ems.2018.2.15-25
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Strategy Formulation Drivers on Strategic Performance

Abstract: To optimize scarce resources firms, need to formulate strategies that will enable them to achieve and sustain competitive advantage. The objective of the study was to propose recommendations to managers of MNCs operating in the mobile telecommunication sector in Nigeria on how to enhance and sustain strategic performance base on the evaluation of strategy formulation drivers. The focus on company vision, mission and long-term objectives helps to bring about new insights on the impact of strategy formulation dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Innovation means focusing on improving existing processes, procedures, products and/or services or creating new ones. This kind of innovation happens, usually, in markets where innovation determines the success or failure of a product (Chijioke et al, 2018;Coltrain et al, 2000;Irfan and Wang, 2019;Mancini et al, 2019). Coordination instead involves the arrangements or agreements between firms over some activities and/or initiatives in the value chain.…”
Section: Competitive Strategy In the Agri-food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Innovation means focusing on improving existing processes, procedures, products and/or services or creating new ones. This kind of innovation happens, usually, in markets where innovation determines the success or failure of a product (Chijioke et al, 2018;Coltrain et al, 2000;Irfan and Wang, 2019;Mancini et al, 2019). Coordination instead involves the arrangements or agreements between firms over some activities and/or initiatives in the value chain.…”
Section: Competitive Strategy In the Agri-food Industrymentioning
confidence: 99%
“…Innovation means focusing on improving existing processes, procedures, products and/or services or creating new ones. This kind of innovation happens, usually, in markets where innovation determines the success or failure of a product (Chijioke et al. , 2018; Coltrain et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In their study on effects of strategic management drivers on the performance of hotel industry in Kenyan Coast, Mutindi, Namusonge and Obwogi (2013) found that adopting key strategic drivers such as Information Communication Technology and customer relationship management had a significant influence on firm competitiveness. Chijioke, Vu and Olatunji (2018) influence of strategic drivers on performance of government organizations in Malawi found that as a result of focusing on human capital and customers as strategic drivers, firm strategies were achieved thus enhancing competitiveness. On the other hand, Porck, Knippenberg and Groenen (2020) in their study on strategic management drivers and firm performance; a case of financial institutions in Pakistan established that strategic drivers only contributed to minimal success of a strategy and had insignificant direct relationship with firm competitiveness.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…it can be defined it is a holistic approach that explains how organizations attain their several strategies for instance in terms of marketing, finance, promotion, delivery, and even customer service strategies (Kim et al, 2008). On the other side, giving more attention to the vision of the organization during the Strategy formulation process is a critical and important element in improving strategic performance (Chijioke et al, 2018). Despite the importance of financial performance as a measure of the organization's activities, strategic performance is of paramount importance in terms of helping the organization to transform and implement its vision and strategy into a set of integrated strategic goals and scales to evaluate the organization's activities and thus predict future events (Al-Qashash, 2020).…”
Section: Strategic Performancementioning
confidence: 99%